2012
DOI: 10.1038/pr.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic lamellar body count and congenital diaphragmatic hernia in humans and in a rat model

Abstract: Background:We examined the extent of fetal lung hypoplasia and lung maturation using the amniotic lamellar body count (LBc) in congenital diaphragmatic hernia (cDh). Methods: We obtained 30 amniotic fluid samples from human cDh cases during cesarean section. We assessed LBc, magnetic resonance imaging (MRI), and ultrasound findings for predicting the prognosis of cDh. We collected newborn amniotic fluid and lung tissue at embryonic day (e)21 from normal and nitrofeninduced cDh rats (administered 100 mg orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Scale bars, 100 nm. E, A lung lamellar body from a rat type II alveolar cell analyzed by thin section EM (from Reference ). Scale bar, 1 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Scale bars, 100 nm. E, A lung lamellar body from a rat type II alveolar cell analyzed by thin section EM (from Reference ). Scale bar, 1 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Saireito is known to increase endogenous corticosteroid production and decrease phosphodiesterase activity, which might also explain the improved respiratory functions in CDH pups treated with Saireito. Our results revealed that fetal lung maturation was not significantly different between the normal, CDH, and CDH + S groups, which is consistent with the recently reported results (Boucherat et al ., ; Watanabe et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Timed pregnant Sprague-Dawley rats were purchased from Chubu Kagaku Shizai (Nagoya, Japan). Rats were exposed to nitrofen (Sigma-Aldrich, Tokyo, Japan) on day 9 of pregnancy (E9), as previously described (Watanabe et al, 2013). Nitrofen (100 mg) was dissolved in 1 mL of olive oil, and control animals were treated with 1 mL of olive oil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations